2017
DOI: 10.1177/1934578x1701200726
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Umbilicaria crustulosa and U. cylindrica

Abstract: The chemical composition of ether, ethyl acetate and dichloromethane extracts of Umbilicaria crustulosa and U. cylindrica were determined for the first time by HPLC-UV, GC-FID and GC-MS. The HPLC-UV analysis was revealed the presence of methyl orsellinate, lecanoric acid, crustinic acid, gyrophoric acid and atranorin in U. crustulosa extracts while in U. cylindrica extracts were detected following compounds: salazinic acid, norstictic acid, atraric acid, gyrophoric acid and atranorin. GC-FID and GC-MS analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 2 publications
(2 reference statements)
0
16
0
Order By: Relevance
“…The parent ion produced major diagnostic MS ions at m / z 373.0568, 357.0618, and 151.0392, confirming this derivative, unlike constictic acid whose daughter ions were at m / z 373.0565, 357.0614, 283.0601, and 227.0698. Peak 23, with a [M − H] − pseudomolecular ion at m / z 371.0412, was identified as norstictic acid [ 36 ], which showed diagnostic daughter ions at m / z 283.0616, 267.0667, 243.0292 and 227.0348. α-alectoronic acid was assigned to peak 41 (molecular anion at m / z 511.1973). The fragmentation of peak 41 produced ions at m / z 467.2050, 369.1338 and 247.0974.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parent ion produced major diagnostic MS ions at m / z 373.0568, 357.0618, and 151.0392, confirming this derivative, unlike constictic acid whose daughter ions were at m / z 373.0565, 357.0614, 283.0601, and 227.0698. Peak 23, with a [M − H] − pseudomolecular ion at m / z 371.0412, was identified as norstictic acid [ 36 ], which showed diagnostic daughter ions at m / z 283.0616, 267.0667, 243.0292 and 227.0348. α-alectoronic acid was assigned to peak 41 (molecular anion at m / z 511.1973). The fragmentation of peak 41 produced ions at m / z 467.2050, 369.1338 and 247.0974.…”
Section: Resultsmentioning
confidence: 99%
“…The fragmentation of peak 41 produced ions at m / z 467.2050, 369.1338 and 247.0974. Finally, peaks 11, 16, 22, 25 and 48 were identified as salazinic acid, connorstictic acid, substictic acid, hypoconstictic and lobaric acid [ 36 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of the HPLC signals revealed that the extraction ability of the solvents decreased in the following order: acetone, ethyl acetate, diethyl ether, dichloromethane (ratio of HPLC signals intensity A:E:EA:DCM = 1.6:1.3:1.3:1), similar to the results of a previous study of lichen extracts. 23…”
Section: Hplc-uv Analysismentioning
confidence: 99%
“…An informative result reported by Serina et al (1996) is the coincidence of gyrophoric acid and hiascic acid in their samples, so the co-occurrence of these two tridepsides in our investigated ecotypes was plausible. Based on the literature (Hestmark, 1991;Krog and Swinscow, 1986;Krzewicka, 2004;Krzewicka and Osyczka, 2002;Manojlović et al, 2012;Narui et al, 1998Narui et al, , 1996Poelt and A c c e p t e d m a n u s c r i p t Nash, 2006;Posner et al, 1992;Serina et al, 1996;Upreti and Pant, 2008;Zlatanović et al, 2017) presence of umbilicaric acid in all of the U. aprina ecotypes is also admissible.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Phytochemical analysis of Umbilicaria species by several authors, has revealed the presence of ca. 16 compounds including gyrophoric acid, lecanoric acid, umbilicaric acid, hiascic acid, ovoic acid, crustinic acid, lasallic acid, usnic acid, norstictic acid, salazinic acid, atraric acid, atranorin, unknown terpenoids, methyl orsellinate, methyl β-orcinolcarboxylate and ethyl hematomate (Hestmark, 1991;Krog and Swinscow, 1986;Krzewicka, 2004;Krzewicka and Osyczka, 2002;Manojlović et al, 2012;Narui et al, 1998Narui et al, , 1996Poelt and Nash, 2006;Posner et al, 1992;Serina et al, 1996;Zlatanović et al, 2017).…”
Section: Introductionmentioning
confidence: 99%